Natural History Studies in NCL and Their Expanding Role in Drug Development: Experiences From CLN2 Disease and Relevance for Clinical Trials - Nickel, Miriam; Schulz, Angela (Frontiers in Neurology, 2022)
Conducting clinical trials in rare diseases is challenging. In trials that aim to use natural history control cohorts for evaluation of efficacy, lack of data on natural history of disease prolongs development of future therapies significantly. Therefore, collection of valid natural history data in clinical settings is needed to advance drug development. These data need to fulfill requirements on type of collection, quantifiable measures on the course of disease, verification and monitoring as well as compliance to strict data protection and sharing policies. Disease registries can be a source for patient data. Late-infantile CLN2 disease is characterized by rapid psychomotor decline and epilepsy. Natural-history data of 140 genotype-confirmed CLN2 patients from two independent, international cohorts were analyzed in a natural history study. Both datasets included quantitative ratings with disease-specific clinical scores. Among 41 patients for whom longitudinal assessments spanning an extended disease course were available within the DEM-CHILD DB (an international NCL disease patient database, NCT04613089), a rapid loss of motor and language abilities was documented in quantitative detail. Data showed that the course of disease is highly predictable with regard to the loss of language and motor function and that the results were homogeneous across multiple and international sites. These data were accepted by EMA and FDA as valid natural-history controls for the evaluation of efficacy in experimental therapies for CLN2 disease and led to an expedited approval of intracerebroventricular enzyme replacement therapy with cerliponase alpha in May 2017.